Social Support and Self-Efficacy of Motivation: A Study of SMP Islamic Hope of Integrated Insan, Karawang, West Java - Ainy Sa’dijah, Nur; Ayu Ganis P, Randwitya; Amaliawati, Lis (International Journal of Psychosocial Rehabilitation, 2020)
Fundamentally, self-efficacy can move the students' motivation in the face of failure so as to have the endurance to resolve every problem in their learning. High confidence with social support makes students motivated to continue learning.